Principles of heat transfer - Kreith, Frank (International Textbook Company, 1965)
Introduce the principles of heat transfer using the classic that sets the standard of coverage and organization for all other heat transfer texts. Following the recommendations of the ASME Committee on Heat Transfer Education, Kreith/Manglik's PRINCIPLES OF HEAT TRANSFER, 8E provides a comprehensive engineering approach that is ideal for your upper-level, one-semester course in heat transfer. This relevant book recognizes that in today's world, computational analysis is more critical than rote mathematical solutions to heat transfer problems.